Physical activity during the early years of life and osteoporosis in adulthood: study among users of the Brazilian National Health System - Bruna Camilo Turi; Jamile Sanches Codogno; Kyle Robinson Lynch; Lia Grego Muniz de Araújo; Bruna Locci; Henrique Luiz Monteiro
ABSTRACT The objectives of this study were to analyze the association between osteoporosis and current/early physical activity and also to identify whether early sport participation, osteoporosis, age and sex are somehow connected. The study sample included 963 participants. Osteoporosis was diagnosed through medical records. Physical activity in current and the early years of life, age, sex and economic condition were assessed through questionnaires. Abdominal obesity was identified by waist circumference. Results showed that osteoporosis was associated with female sex and higher age. Participants that were active in adulthood had 47% lower chance of osteoporosis (odds ration [OR] = 0.53[0.30-0.93]). Adults that were active in childhood and adolescence had a lower chance of osteoporosis only in the crude model (OR = 0.38[0.22-0.64]). Women that were inactive in their youth were almost five times more likely to have osteoporosis when compared to men under the same conditions (OR = 4.80[2.46-9.37]). A lack of sports participation in the early years of life seems to be associated with osteoporosis, age and sex.